Comparison of the Isotopic Composition of Hg and Pb in Two Atmospheric Bioaccumulators in a Pyrenean Beech Forest (Iraty Forest, Western Pyrenees, France/Spain) - Barre, Julien P. G.; Queipo-Abad, Silvia; Sola-Larrañaga, Cristina; Deletraz, Gaëlle; Bérail, Sylvain; Tessier, Emmanuel; Elustondo Valencia, David; Santamaría, Jesús Miguel; de Diego, Alberto; Amouroux, David (Frontiers in Environmental Chemistry, 2020)
Mercury (Hg) and lead (Pb) isotopic compositions were investigated in mosses and lichens collected in a large mountainous beech forest (Iraty Forest) located on the French-Spanish Pyrenean border. Hg isotopic signature in topsoil samples were also analyzed in selected sampling sites. This is the first work that uses the complementary information of both isotopic systems in two distinct atmospheric bioaccumulators. Mosses and lichens present characteristic accumulation due to their integration times, displaying different information on metal pollution over the area. Hg and Pb concentrations in annual moss shoots represent recent atmospheric accumulation, while whole lichen thalli integrates a process of accumulation over a longer period. Lead isotope ratios in mosses are consistent with reported data corresponding to the actual European atmospheric background (206Pb/207Pb ~1.158), while Hg isotopic composition reflects potential uptake of both dry and wet Hg depositions. For lichens, Pb isotopic composition exhibits the contribution of a longer integration period of both industrial Pb emissions and legacy of leaded gasoline pollution. Hg isotopes in lichens discriminate two main groups: a larger one representing the background atmospheric contribution and a second one corresponding to unexpected higher Hg content. The similarities in odd and even Mass-independent fractionation (MIF) of Hg isotopes between topsoils and lichens from the larger group, support the idea that foliage uptake is the main input of Hg in soils. The second group of lichens exhibits more negative δ202Hg (down to -4.69‰) suggesting a new source of fractionation in this area, probably related to lichens aging and/or stubble and grass fires due to pastoral activities. This study demonstrates that using both Hg and Pb isotopic signature in lichens and mosses allows to trace atmospheric sources and environmental pathways of these metals in forested ecosystems. The new data set in a remote environment provides also new information on the fate of atmospheric Pb and Hg depositions.